Providers' Perceptions of Student Pharmacists on Inpatient General Medicine Practice Experiences - Lancaster, Jason W. (American Journal of Pharmaceutical Education, 2013)
Objective. To assess health care providers’ perceptions of student pharmacists involved as members of a general medicine team. Methods. A brief, anonymous, online survey instrument was distributed to 134 health care providers at 4 major medical centers in Massachusetts who interacted with Northeastern University student pharmacists during inpatient general medicine advanced pharmacy practice experiences beginning in March 2011. The survey instrument assessed health care provider perception of student pharmacists’ involvement, preparedness, clinical skills, and therapeutic recommendations. Results. Of the 79 providers who responded, 96.2% reported that student pharmacists were prepared for medical rounds and 87.3% reported that student pharmacists were active participants in patient care. Also, 94.9% and 98.7% of providers indicated that student pharmacist recommendations were appropriate and accurate, respectively. The majority (61.8%) of providers believed that student pharmacist involvement on internal medicine teams was beneficial. Conclusions. Provider perceptions regarding student pharmacist participation on general medicine practice experiences were mostly positive.